PROSPEK BISNIS TANAMAN HIAS DI MASA PANDEMI COVID-19 (Studi Kasus pada Alhuda Bussiness Community Pekanbaru) - Asnahwati, Asnahwati (Eko dan Bisnis: Riau Economic and Business Review, 2021)
In the midst of the Covid-19 pandemic that hit this country, the public was again shocked by the fever of ornamental plants that began to become epidemic. This time it was not only women who were infected with flower fever or ornamental plants but also Adam. People are getting tired of staying at home or working from home. Day by day the demand for ornamental plants is increasing. In addition to the old traders who were busy fulfilling market demand, impromptu ornamental plant traders began to appear. Many people are starting to switch to the ornamental plant business. As time goes by, the number of traders continues to grow. But lately the group of ornamental plant hunters began to appear less. Both in parks that sell ornamental plants and in markets in Pekanbaru. Turnover of farmers or ornamental plant traders began to decline. However, the number of ornamental plant traders who enter the market is not decreasing but even increasing. Therefore, this study was conducted to find out what the future prospects of this ornamental plant business will be during the Covid-19 Pandemic. The formulation of the problem from this research is how the business prospects of ornamental plants are seen from the perception of "Alhuda Business Community". The population in this study were all members of the "Alhuda Business Community" which amounted to 73 people and all of them were used as samples or respondents with census techniques. The data analysis method used in this research is descriptive qualitative. The results of the study found that: a) The ornamental plant business is a business opportunity that is quite promising in the future. b) Ornamental plants are able to green the yards of houses in urban areas and prevent air pollutionIn the midst of the Covid-19 pandemic that hit this country, the public was again shocked by the fever of ornamental plants that began to become epidemic. This time it was not only women who were infected with flower fever or ornamental plants but also Adam. People are getting tired of staying at home or working from home. Day by day the demand for ornamental plants is increasing. In addition to the old traders who were busy fulfilling market demand, impromptu ornamental plant traders began to appear. Many people are starting to switch to the ornamental plant business. As time goes by, the number of traders continues to grow. But lately the group of ornamental plant hunters began to appear less. Both in parks that sell ornamental plants and in markets in Pekanbaru. Turnover of farmers or ornamental plant traders began to decline. However, the number of ornamental plant traders who enter the market is not decreasing but even increasing. Therefore, this study was conducted to find out what the future prospects of this ornamental plant business will be during the Covid-19 Pandemic. The formulation of the problem from this research is how the business prospects of ornamental plants are seen from the perception of "Alhuda Business Community". The population in this study were all members of the "Alhuda Business Community" which amounted to 73 people and all of them were used as samples or respondents with census techniques. The data analysis method used in this research is descriptive qualitative. The results of the study found that: a) The ornamental plant business is a business opportunity that is quite promising in the future. b) Ornamental plants are able to green the yards of houses in urban areas and prevent air pollution